Analisis Strategi Pengembangan Produk dalam Meningkatkan Daya Saing pada Usaha Dodol Tiga Putri di Singengu Kecamatan Kotanopan - Muji Rahayu; Habibatur Ridhah (ARZUSIN, 2026)
Competition among traditional food businesses is becoming increasingly intense, but studies that specifically discuss product development strategies in improving the competitiveness of locally based dodol businesses remain limited. This study aimed to analyze product development strategies in improving the competitiveness of the Tiga Putri Dodol Business in Singengu Village, Kotanopan Subdistrict. This study used a qualitative approach with a case study design, involving the business owner as the main informant and consumers as supporting informants selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed descriptively using the Ansoff Matrix. The results showed that competition among dodol businesses was relatively high, with eight business actors, while the Tiga Putri Dodol Business had a market share of below 10% despite experiencing an increase in revenue. The products produced were still limited to one flavor variant with relatively uniform traditional packaging, resulting in low product differentiation. In addition, the conventional marketing system caused limited market reach. Based on the Ansoff Matrix analysis, the relevant strategy is product development through increasing product variety and quality. These findings contribute to the development of marketing strategy and MSME competitiveness studies, while also broadening understanding of the importance of product innovation in the context of traditional food businesses. The conclusion of this study confirms that product innovation and strengthening marketing strategies are necessary to improve the competitiveness of the Tiga Putri Dodol Business, with support from business actors and the government in the development of locally based MSMEs.